2015
DOI: 10.1016/j.stem.2015.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Premigratory and Migratory Neural Crest Cells Are Multipotent In Vivo

Abstract: The neural crest (NC) is an embryonic stem/progenitor cell population that generates a diverse array of cell lineages, including peripheral neurons, myelinating Schwann cells, and melanocytes, among others. However, there is a long-standing controversy as to whether this broad developmental perspective reflects in vivo multipotency of individual NC cells or whether the NC is comprised of a heterogeneous mixture of lineage-restricted progenitors. Here, we resolve this controversy by performing in vivo fate mapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
158
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(169 citation statements)
references
References 28 publications
10
158
0
1
Order By: Relevance
“…5). Given that thoracic crest will produce enteric neurons when transposed rostrally (32) and, more generally, that neural crest cells are not specified before migration (33,34), the restriction of the dual sympatho-enteric fate to the cervical and sacral levels of the trunk crest is likely to stem, less from cell-intrinsic fate restriction than from topological factors, such as the continuity of the peri-aortic and foregut mesenchymes at one end, and the contiguity of the pelvic ganglion-a "staging site" for the enteric sacral crest (30,35)-to the rectum at the other end.…”
Section: Discussionmentioning
confidence: 99%
“…5). Given that thoracic crest will produce enteric neurons when transposed rostrally (32) and, more generally, that neural crest cells are not specified before migration (33,34), the restriction of the dual sympatho-enteric fate to the cervical and sacral levels of the trunk crest is likely to stem, less from cell-intrinsic fate restriction than from topological factors, such as the continuity of the peri-aortic and foregut mesenchymes at one end, and the contiguity of the pelvic ganglion-a "staging site" for the enteric sacral crest (30,35)-to the rectum at the other end.…”
Section: Discussionmentioning
confidence: 99%
“…It is also noteworthy that a pool of multipotent postmigratory NC progenitors (47,48), some of which express cKit (49), has been recorded in other tissues; hence, it would be interesting to examine their relationship to CNC kit . Our study differs from a recent cardiac genetic fate-map of cKit, using different cKit alleles (21).…”
Section: Discussionmentioning
confidence: 99%
“…Baggiolini and colleagues used the Confetti transgene, combined with inducible, tissue-specific promoters driving Cre recombinase, to answer a long controversial issue regarding the potency of neural crest cells before and after they leave the neural tube. Using rigorous statistical methods to exclude redundant recombination events, they found that most neural crest cells are multipotent both pre- and postmigration, but that their fates can be heterogeneous, as seen by variation in the range of differentiated fates in different clones (Baggiolini et al, 2015). …”
Section: Clonal Analysis Within Cell Lineagesmentioning
confidence: 99%